Implementasi Algoritma Dijkstra Rute Terpendek pada Aplikasi WisKul PasMing - Muhamad Reza Pahlevi; Ratih Titi Komalasari (KITA Institute, 2022)
Indonesia is famous for its various kinds of culinary tourism and spread in various areas of the city of Jakarta. Various types and locations of culinary make it difficult for local and foreign tourists to find and choose culinary dishes and the routes to culinary locations in Jakarta are very numerous and varied, especially foreign tourists. Therefore, the author tries to make an android-based culinary tourism location search application in the hope that it can provide a lot of culinary location information with the fastest and closest tracks, and is equipped with a map of culinary tourism locations. The algorithm used to find the shortest track uses the Dijkstra algorithm. The Dijkstra algorithm is a search algorithm for the shortest track based on the smallest track (edge) from the implementation location to the destination culinary tourism location. Culinary tourism area data and road data obtained from Google Earth and Google maps. From the origins of the trial of instances which have been done, it could be visible that the application has succeeded in implementing the Dijkstra solving procedure in finding the shortest route to culinary locations. This study produces the following distance node values BCDEJIF, ABCDFGHINM, MNIFDCBAE, BAEJNMLKHG, ABCDFGHIJE ABCDFGHILM, ABCGHKLMNIJE.